Contractual Concepts in the Civil Code of The Republic of Uzbekistan and and Their Implementation in Electronic Contracts for E-Commerce (Eurasian Journal of History, Geography and Economics, 2023)
This article examines the concepts and types of contracts in the Civil Code of the Republic of Uzbekistan, forms of contracts, negotiation of acceptance and offer in traditional contracts and electronic documents, the main conditions for concluding contracts and the interpretation of these articles for electronic contracts. The article also noted the composition of the agreement based on the country's legislative acts.